PEDAGOGICAL FOUNDATIONS OF QUALITY ORGANIZATION OF EDUCATION ON THE BASIS OF COOPERATION IN HIGHER EDUCATION (Universal International Scientific Journal, 2026)
This article analyzes the theoretical and pedagogical foundations of the organization of cooperative education in higher education institutions, its role in the quality of education and the development of students' professional competencies. The essence, forms and methods of cooperative education technologies are highlighted, and the conditions for their effective implementation in the higher education process are indicated. The results of the study confirm that cooperative education increases students' independent thinking, teamwork skills, and creative activity.
Keywords: collaborative education; higher education; education quality